The role of social influences and cognitive self-regulation in supporting cancer patients to engage in physical activity - Ungar, Nadine (2015)
Cancer patients are recommended to engage in regular physical activity, as research has identified various beneficial effects of exercise both during and after medical treatment (Schmitz et al., 2010; Speck, Courneya, Mâsse, Duval, & Schmitz, 2010). Most cancer patients are motivated to adopt a healthy lifestyle including regular physical activity (Demark-Wahnefried, Aziz, Rowland, & Pinto, 2005). However, it has been shown that only a minority of cancer patients meet the exercise guidelines (Blanchard, Courneya, & Stein, 2008). This thesis aims to (1) determine factors that explain the (low) level of physical activity among cancer patients and (2) help cancer patients to increase their exercise level. Thereby, the first focus of this thesis was placed on cognitive self-regulation examined within the frameworks of the Theory of Planned Behavior (Ajzen, 1991) and the Health Action Process Approach (Schwarzer, 2001, 2008). Self-regulation is assumed to be a relevant factor to adopt and maintain health-enhancing behaviors by bridging the gap between intention and behavior (De Ridder & De Wit, 2006; Schwarzer, 2008). Besides these patient centric self-regulatory factors, social influences have consist-ently been found to be important predictors of physical activity among cancer patients (e.g. Barber, 2012). This thesis adds to previous research by (1) including the perspective of a family member, (2) examining the distinction between social support, social control and its re-lations to reactance, and (3) incorporating role model support in an intervention study. This publication based dissertation comprises three manuscripts, which present results of three different studies. All are part of the MOTIVACTION-project (MOTivational InterVention enhancing physical ACTivity In ONcological patients) and were designed successively to build on each other’s results. The first study applied the Theory of Planned Behavior in a qualitative and a quantitative cross-sectional design. The aim of this study was to elicit a broad spectrum of attitudes – especially negative ones – and to compare already physically active and insuffi-ciently active patients within the framework of the Theory of Planned Behavior. Attitude turned out to be a relevant predictor of the intention to exercise for insufficiently active patients, whereas social influences were especially important to maintain an active lifestyle. Additionally, self-efficacy discriminated best between active and insufficiently active patients. The second study was a longitudinal study among patients and their family members. Through this design, the relation between perceived and relative-reported social support and control could be determined (moderate associations occurred). Gender differences revealed that female patients perceived and received less support and control by their relatives. Fur-thermore, reactance might especially impede male patients to build up a physically active lifestyle. Relative-reported social support was the only significant predictor of physical activity at follow-up. Finally, the third study was a behavior change intervention designed as a randomized controlled trial. It compared an exercise intervention focusing on self-regulation strategies from the Health Action Process Approach and role model support with stress management training. The exercise intervention was able to increase the physical activity level especially among patients who realized contact with a role model. Thus, the combination of self-regulation and social influence turned out to be most effective. All in all, this thesis provides encouraging results that cognitive self-regulation and social influences can explain and increase the physical activity level of cancer patients.